Webquest as an opportunity of formation at student’s competence and competencies - Natalia N. Kasatkina; Natalija A. Lichak (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The results of the method of intensification of educational activities of students using web quest technology in practice to increase their motivation to learn a foreign language. The authors present a method of using the modern scenario of the organization of project activities of students on the topic using the resources of the Internet. It includes the use of technical tools in the classroom - a variety of applications and thematic sites. The information-communication technologies which allow to carry out search, collection, storage, processing, dissemination of information when learning a foreign language. When performing the tasks of the web quest, two experimental groups were identified in order to form pedagogical competence. The evaluation of group activities was carried out on the basis of news presentations of each column. Since the content and categories of web quests differed from each other, it was difficult to compare the results. However, the submissions of the students who prepared the web quests were found to be satisfactory and included in the results and assessment data sheet. Was recorded formed the competence, the possession of which determined the result in the performance of independent work on the web quest.